Student Leadership Competencies Development During The Covid-19 Pandemic For Higher Learning Institution - Abd Kadir, Ermeey (Advances in Humanities and Contemporary Studies, 2022)
This research’s primary goal was to understand attributes for developing student leadership competencies that emerged following the covid-19 pandemic. This study employed a qualitative approach. Throughout various methods applied in this research occurred due to the combination within interview sessions, focus group interviews, documentation review, and casual talks with a group of current and previous student leaders. The findings indicate that several attributes influence the development of student leadership competencies: 1) Emotional intelligence, self-belief, confidence, and responsiveness are all individual characteristics.; 2) Academic activities, student and faculty interactions, peer interactions, and leadership positions in the group and student organisations are all examples of student experiences and involvement.; and 3) Institutional constraints, such as financial constraints. The study’s conclusions guide practitioners such as student affairs staff, academics, and the higher learning ministry regarding the best strategies for training future leaders to lead effectively during and after a pandemic.